Vimentin-Rab7a Pathway Mediates the Migration of MSCs and Lead to Therapeutic Effects on ARDS. (29th July 2021) - Wang, Kai; Du, Boxiang; Zhang, Yan; Wu, Congyou; Wang, Xiuli; Zhang, Xu; Wang, Liwei
Abstract : Acute respiratory distress syndrome (ARDS) is difficult to treat and has a high mortality rate. Mesenchymal stem cells (MSCs) have an important therapeutic effect in ARDS. While the mechanism of MSC migration to the lungs remains unclear, the role of MSCs is of great clinical significance. To this end, we constructed vimentin knockout mice, extracted bone MSCs from the mice, and used them for the treatment of LPS-induced ARDS. H&E staining and Masson staining of mouse lung tissue allowed us to assess the degree of damage and fibrosis of mouse lung tissue. By measuring serum TNF- α, TGF- β, and INF- γ, we were able to monitor the release of inflammatory factors. Finally, through immunoprecipitation and gene knockout experiments, we identified upstream molecules that regulate vimentin and elucidated the mechanism that mediates MSC migration. As a result, we found that MSCs from wild-type mice can significantly alleviate ARDS and reduce lung inflammation, while vimentin gene knockout reduced the therapeutic effect of MSCs in ARDS. Cytological experiments showed that vimentin gene knockout can significantly inhibit the migration of MSCs and showed that it changes the proliferation and differentiation status of MSCs. Further experiments found that vimentin's regulation of MSC migration is mainly mediated by Rab7a. Rab7a knockout blocked the migration of MSCs and weakened the therapeutic effect of MSCs in ARDS. In conclusion, we have shown that the Vimentin-Rab7a pathway mediates migration of MSCs and leads to therapeutic effects in ARDS.